Illicit ketamine induced frequency of micturition in a young Malay woman - Robson, N.Z.; Vicknasingam, B.; Narayanan, S. (2010)
Issues. The growing use of illicit ketamine among young adults poses a public health concern in Malaysia. In contrast to medical use of ketamine, illicit use has been reported to produce adverse effects on the urinary tract and, in particular the bladder. Approach and Key Findings. This case report describes a young Malay woman who developed severe bladder symptoms (urinary frequency) after consuming illicit ketamine. A history of illicit ketamine use was initially missed, and she was consequently diagnosed and treated for a urinary tract infection. Her symptoms persisted despite several courses of antibiotics. The patient was subsequently referred to an urologist where cystoscopic examination and biopsy of the bladder found changes consistent with interstitial cystitis. This was despite the absence of haematuria. Renal function was normal. Implication. The patient's ketamine use was the most likely cause for the urinary symptoms and bladder changes. Conclusion. Illicit ketamine use may lead to severe urinary tract problems that can be irreversible even after ketamine has ceased. Early diagnosis is critical although difficult when ketamine use is not divulged during the consultation with the physician. Physician consideration of this new clinical entity is important, particularly in cases where the symptoms do not resolve with usual treatment. [Robson N, Vicknasingam B, Narayanan S. Illicit ketamine induced frequency of micturition in a young Malay woman. Drug Alcohol Rev 2010;29;334-336].